The digital age students: Exploring leadership, freedom, and ethical online behavior: A quantitative study - Mohamed Mekheimer; Walid Mohamed Abdelhalim (Social Sciences and Humanities Open)
This study investigates the complex interplay between leadership skills, personal freedom, and digital responsibility among 1226 university students in Egypt, addressing a critical need to understand student-led online behavior. Employing validated questionnaires and a quantitative, cross-sectional design, we examined the predictive relationships among these constructs. Findings revealed significant positive correlations between leadership skills and digital responsibility, underscoring that developing strategic vision, communication, motivation, and ethical decision-making significantly enhances responsible online conduct. Notably, while leadership skills predicted both digital responsibility and personal freedom, public freedom emerged as a particularly robust predictor of digital responsibility. This highlights the importance of empowering students within the public sphere to foster ethical digital practices. The study underscores the need for a comprehensive approach that cultivates both leadership capabilities and responsible civic engagement to promote ethical and sustainable digital citizenship. While acknowledging the limitations of our cross-sectional design, which precludes causal inferences, and the need for further research across diverse contexts, this study provides a valuable framework for future longitudinal investigations into the complex dynamics of digital responsibility.